Synthesis of Stable Sols of Layered Titanate Nanoparticles using Dialysis and Applications for Thin Film Preparation - Wen, Chun Ming; Kojima, Takashi; Uekawa, Naofumi (Journal of Applied Solution Chemistry and Modeling, 2015)
Sols with stable dispersion of layered titanate nanoparticles were prepared at 298 K using dialysis of a mixed solution of ethylene glycol, TiCl3, ammonium carbonate, and H2O2. Raman spectra of the particles in the obtained sols showed Raman scattering peaks which can be assigned to a layered titanate structure. The stability of the obtained sols depended on the molar ratio of [ammonium carbonate] / [Ti ion]. The molar ratios of 3, 4, and 5 produced transparent yellow stable sols. Peptization of titanium hydroxide precipitate with H2O2 formed stable sols with dispersion of layered titanate nanoparticles, which had plate - shaped morphology. The obtained sols formed layered titanate thin films on glass substrates easily by drying the sols. Furthermore, when the layered titanate thin films were heated at 773 K for 1 h, anatase TiO2 thin films were obtained with (101) orientation of crystallites and optical transparency.